The Conjunction of the Conditional Adverbial (Lammā) With the Letters (Fāʾ) and (Wāw) in Surat Yusuf: A Novel Functional Interpretation - Al-Rayahneh, Fadi Mahmoud; Awawdeh, Fatina Jamal (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: study aims to reveal conditional adverbial function of (Lammā) when it’s combined with (Fāʾ) and (Wāw), as it has taken Surah Yusuf as a subject for applied study, since the surah is characterized by large number of events that can be summed up, the context of the situation contributed to not mentioning them, in order that the recipient could appreciate them without difficulty. Methods: The study adopts modern functional method, as its scholars have researched linguistic tools in Arabic and contemplated semantic function, analyzed the sentence and looked closely at its inflection, clarified its meanings, explained apparent formal connections and showed its implicit order in its coherence and the importance that tools add to constructing sentences and conveying meanings. Results: template model contributes to the analysis of linguistic expression of vocabulary. It allocates elements and gives the concept breadth, it takes in consideration internal and external components of sentence. The conditional sentence carries the meaning of the penalty between the conditional verb and its answer, and the letter (Lammā) gives when it is combined with the (Wāw) a broad significance in time. Conclusions: When (Lammā) is combined with (Wāw), time becomes extended to accommodate number of inter-events that occur between conditional verb and answer, and most likely the recipient interprets them and the picture is complete for him. When (Lammā) is combined with the (Fāʾ), time becomes accelerated, the two verbs in the conditional sentence follow each other.